Quality assessment system for teaching activities - V. Petruk, Galina (2019)
The specialist training quality in the higher education system directly depends on the effectiveness of the teaching staff in universities. This paper presents the methodological aspects of assessing the quality of teaching activities in universities. The quality assessment of teachers’ work should be based on the quality of educational services they provide, which can be measured from two points of view: the compliance of the achieved educational results with accepted state standards and their compliance with the demands of consumers (students). One of the most important modern approaches to personnel assessment is the competency-based approach, which allows us to give the most objective picture of the professionally important qualities of employees. The paper analyzes the main methods of assessment of the teaching staff and highlights the assessment criteria. It is proposed to use a number of principles in order to ensure the effectiveness of the teacher assessment system. In practice, the quality assessment of the teaching activities should be a system, the totality of the elements of which makes it possible to reliably identify the potential of teachers and provide quality training for future specialists in a higher educational institution.